Allosteric Inhibitors of NMDA Receptor Functions - William F. Borschel; Gabriela K. Popescu; Swetha Murthy (Pharmaceuticals, 2010)
NMDA receptors are glutamate-activated ion-channels involved in many essential brain functions including learning, memory, cognition, and behavior. Given this broad range of function it is not surprising that the initial attempts to correct NMDA receptor-mediated pathologies with en-mass receptor blockade were derailed by unacceptable side effects. Recent successes with milder or more targeted pharmaceuticals and increasing knowledge of how these receptors operate offer new incentives for rational development of effective NMDA receptor-targeted therapies. In this article we review evidence that L-alanine, a glycine-site partial agonist and pregnanolone sulfate, a use-dependent allosteric inhibitor, while attenuating NMDA receptor activity to similar levels elicit remarkably dissimilar functional outcomes. We suggest that detailed understanding of NMDA receptor activation mechanisms and of structural correlates of function will help better match modulator with function and neurological condition and may unleash the yet untapped potential of NMDA receptor pharmaceutics.